2017
DOI: 10.22146/tradmedj.24312
|View full text |Cite
|
Sign up to set email alerts
|

BIOACTIVE COMPOUNDS FROM TORBANGUN [Plectranthus amboinicus (Lour.) SPRENG] CHLOROFORM FRACTION INDUCE APOPTOSIS IN BREAST CANCER (MCF-7 CELLS) IN VITRO

Abstract: Torbangun (Plectranthus amboinicus (Lour.) Spreng) is a medicinal plant that has been traditionally used in tropical countries to cure various illnesses. The objective of this study was to identify the active compounds in the chloroform fraction which have effect on the apoptosis-related genes expression of breast cancer MCF-7 cells. Apoptosis was observed morphologically using Hoechst nuclear staining. Expression of the genes was analyzed using Real-Time PCR. Chemical compounds of the plant fractions were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
6
0
3
Order By: Relevance
“…P. amboinicus is used for the treatment of colds, coughs, asthma, and diseases of the respiratory tract in general, as well as to treat headaches, fever, skin diseases, and gastrointestinal disorders [ 17 , 18 , 19 ]. Thus, because it is a well-known species and used by the population, many studies on its effects already exist and demonstrate its antimicrobial and antiviral activities in vitro [ 20 , 21 ], activity against respiratory and gastrointestinal disorders, anticonvulsant, antitumor [ 22 , 23 ], analgesic, anti-inflammatory, and antioxidant activities [ 24 , 25 ]. These two species are also used in culinary as flavorings and in the preparation of some foods [ 17 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. amboinicus is used for the treatment of colds, coughs, asthma, and diseases of the respiratory tract in general, as well as to treat headaches, fever, skin diseases, and gastrointestinal disorders [ 17 , 18 , 19 ]. Thus, because it is a well-known species and used by the population, many studies on its effects already exist and demonstrate its antimicrobial and antiviral activities in vitro [ 20 , 21 ], activity against respiratory and gastrointestinal disorders, anticonvulsant, antitumor [ 22 , 23 ], analgesic, anti-inflammatory, and antioxidant activities [ 24 , 25 ]. These two species are also used in culinary as flavorings and in the preparation of some foods [ 17 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PCR reaction mix for identified HPV comprised 10 pmoL primers forward and reverses, Gotaq master mix PCR (Promega, USA), nuclease-free water, and DNA as a template. The primer used in this study is shown in Table-1 [ 9 - 11 ]. A total of 5 uL of DNA was amplified in a thermal cycler (VerityApplied Biosystem, USA) with PCR condition 95°C for 4 min, denaturation 95°C for 30 s, annealing 54°C for 30 s, and extension 72°C for 30 s. Stage denaturation until the extension was repeated to 40 cycles with amplification using electrophoresis gel agarose 1.8% later visualized in GelDoc2000.…”
Section: Methodsmentioning
confidence: 99%
“…The spots of TLC from isolated results were identified by using UHPLC-MS/MS tandem mass spectrometer (UHPLC Vanquish Tandem Q Exactive Plus Orbitrap HRMS ThermoScientific, column Accucore phenyl hexyl, 100 x 2.1 mm, 2.6 µm). The principle of UHPLC-MS/MS refers to Yulianto et al (2017) and Maser et al (2015). Spots extract were diluted with 100 μL methanol and then filtrated by filter membrane 0.45 µm.…”
Section: Sample Identification With Bioactive Chemical Profile With Tmentioning
confidence: 99%